The Influence of Pregnancy on Female Prostate Morphophysiology in Gerbils (Meriones unguiculatus) (Feb, 10.1007/s43032-021-00475-9, 2021) - Jesus Gomes, Lorranny de (2021)
Univ Fed Goias, Dept Histol Embryol & Cell Biol, Microscopy Lab Appl Reprod, Av Esperanca S-N,Campus Samambaia, BR-74690900 Goiania, Go, Brazil